Características pós-abate de bovinos terminados em confinamento recebendo ou não restrição alimentar - Silva, Mauren Burin da (2018)
The objective of this study was to evaluate the effect of feed restriction on the carcass and meat characteristics of finished feedlot under high grain diets. Twenty - seven surgically castrated cattle, from the crossing of the Charolais and Nelore races, were used, with age and average slaughter weights of 30 months and 410 kg of live weight respectively. The experimental design was completely randomized. The animals were balanced by initial body weight and genetic predominance and afterwards they were divided into three treatments: high grain diet fed ad libitum (Control Treatment, CT); with a restriction of 7.5% of consumption (TR-7.5%); and with a 15% restriction on consumption (TR-15%). Cattle fed with or without food restriction did not significantly affect farm weight, empty body weight, warm and cold carcass weight, and warm and cold carcass yield, cooling breakage, subcutaneous fat thickness, area loin eye, yields of commercial cuts and compactness, proportions between tissues, production of fatty tissues, and for meat quality attributes. However, for the gastric-intestinal content, there was a greater participation in the animals fed at will and a reduction occurred with the inclusion of the food restriction 7.5%. Omaso and abomaso when expressed in absolute weight, there was a decrease in their weight, with increased food restriction, with omaso (2.55, 2.46 and 2.23) and abomaso (1.92, 1, 78 and 1.32), due to this behavior the absolute total digestive tract was lower than the animals that suffer food restriction. Regarding the liver in absolute weight, the mean values (3.90 kg) for CT were higher for TR-15% (3.47 kg). The relative weight spleen also showed a difference between treatments, with 0.29% for animals ad libitum, 0.25% and 0.24% for animals that received 7.5% and 15% of restriction. The different proportions of the treatments also influenced the blood volume, animals fed at will showed higher blood volume (11.23 kg, 3.06%) than those fed with a restriction of 15% (10.53kg, 2.88%). The total number of vital organs showed significant differences for the relative weight, since the organs that make up this total value also presented similar behavior. Higher levels of feed restriction for cattle did not compromise carcass and meat characteristics. However, in relation to the content of the digestive tract and vital organs was lower in animals fed with food restriction.